Seroprevalence of syphilis in reproductive-age female blood donors: a cross-sectional study in Surabaya, Indonesia - Arkha Rosyaria Badrus; Miftahul Khairoh; Cityta Putri Kwarta; Novi Anggraeni; Rakhmalia Imeldawati; Yustisia Amalia; Cipriano do Rosario Pacheco (Universitas Gadjah Mada, 2026)
Purpose: Syphilis remains a global public health concern, particularly in developing countries. This study aims to determine the seroprevalence of syphilis and assess its association with sociodemographic factors among female blood donors of reproductive age in Surabaya, Indonesia. Methods: This cross-sectional study analysed secondary data from 186 female blood donors aged 15–49 years at the Indonesian Red Cross (PMI) in Surabaya. Syphilis status was categorized as reactive or non-reactive based on screening results. Sociodemographic variables included age, marital status, education, and occupation. Descriptive and chi-square bivariate analyses were conducted using JASP 0.95.4, with significance set at p < 0.05. Results: The seroprevalence of syphilis among female donors was 25.3%. Significant associations were found between syphilis status and marital status (p = 0.000), age category (p = 0.001), and education level (p = 0.013). Unmarried women, adolescents aged 15–24, and those with lower levels of education had the highest proportions of reactive results. While occupation was not statistically significant (p = 0.228), students and housewives showed the highest infection rates. Conclusion: The high seroprevalence of syphilis among female reproductive-age donors in Surabaya is significantly associated with specific sociodemographic factors. Strengthening STI prevention programs and routine donor screenings is essential to ensure blood safety and improve reproductive health outcomes.